Three new localities of endemic tigridias from Mexico: Tigridia bicolor, T. matudae and T. vanhouttei spp. roldanii - Rodríguez, Aarón; Ortiz-Catedral, Luis; Heaton, Edmund (Instituto de Ecología, A.C., 2003)
Mexico is the diversity center of the genus Tigridia (Tigridieae: Iridaceae). Its irregular topography and climatic diversity have generated a high number of endemics in this group of plants. We conducted collecting expeditions in Mexico during the summers of 1996 and 2000. The goals of the expeditions were to widen the known geographical distribution of Tigridieae and to collect leaf material, bulbs and seeds for phylogenetic studies of this group of plants. As a result, we found new populations of T. bicolor Molseed, T. matudae Molseed and T. vanhouttei ssp. roldanii Molseed, in Oaxaca, Morelos, and Puebla respectively. These taxa were known only from their type localities. These new localities are presented together with field observations and aspects of phenology.